Review of the family Rivulidae (Cyprinodontiformes, Aplocheiloidei) and a molecular and morphological phylogeny of the annual fish genus Austrolebias Costa 1998 - Loureiro,Marcelo (2018)
ABSTRACT The family Rivulidae is the fourth most diverse clade of Neotropical fishes. Together with some genera of the related African family Nothobranchiidae, many rivulids exhibit a characteristic annual life cycle, with diapausing eggs and delayed embryonic development, which allows them to survive in the challenging seasonal ponds that they inhabit. Rivulidae also includes two species known as the only the self-fertilizing vertebrates and some species with internal fertilization. The first goal of this article is to review the systematics of the family considering phylogenetic relationships and synapomorphies of subfamilial clades, thus unifying information that is dispersed throughout the literature. From this revision, it is clear that phylogenetic relationships within Rivulidae are poorly resolved, especially in one of the large clades that compose it, the subfamily Rivulinae, where conflicting hypotheses of relationships of non-annual and annual genera are evident. The second goal of this work is to present an updated phylogenetic hypothesis (based on mitochondrial, nuclear, and morphological information) for one of the most speciose genus of Rivulidae, Austrolebias. Our results confirm the monophyly of the genus and of some subgeneric clades already diagnosed, but propose new relationships among them and their species composition, particularly in the subgenus Acrolebias.